Art as an expression of the unconscious psyche - Weiner, Elana (Rhodes University, Faculty of Humanities, Department of Psychology, 1988)
This study aimed to investigate the use of expressive art as a manifestation of the unconscious psyche and as an indication of underlying personality dynamics. Its use as a significant medium for therapeutic encounter and exploration was investigated by analysing the art produced by four psychiatric in-patients during their participation in an eight-week art therapy programme. Each patient's art series was qualitatively and thematically interpreted with a focus upon the meaning of significant recurring images and motifs. The results of this study indicate that the particularity of each patient's graphic imagery enabled the lived experience of their struggles and preoccupations to emerge as uniquely different. Through their art productions they revealed the nature of their inner worlds and the power of their thoughts, feelings and experiences.
Keywords: Art -- Psychology; Art and mental illness; Art therapy; Subconsciousness